Character Strengths that Prevent Substance Use in Mexican University Students - Sánchez Hernández, María Enriqueta (2025)
Objective. Identify character strengths that predict non-substance use. Method. Quantitative study with a cross-sectional research design. For data collection, the Spanish version of the VIA-120 Inventory of Strengths Questionnaire was used. To measure substance use, a six-question questionnaire was used regarding the use of alcohol, tobacco, electronic cigarettes, marijuana, non-prescription medication to stay focused or alert, and any illegal drugs. The application was electronical. The sample was non-probabilistic of 569 participants, with an average age of 21.2 years (SD = 2.30). 35.3% were men and 64.7% women. The participants gave their informed consent. A robust regression was performed with the RStudio program. Results. Two character strengths were predictors of non-consumption of substances: Self-regulation and Spirituality.